INDES 2018 By FSKM, UiTM Perak Branch / Siti Salihah Shaffie - Shaffie, Siti Salihah (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
With the theme 'Transformative Innovation: Unlocking The Future', INDES 2018 was successfully held on August 15, 2018 at Kinta Riverfront Hotel Suites, Ipoh, Malaysia. This is the 7th International Innovation, Invention and Design Competition organized by the Faculty of Computer and Mathematical Sciences and co-organised by the Department of Research, Industrial Linkages, Community & Alumni Network, UiTM Perak Branch. The competition aimed to increase research for innovation and support product and proto-type design to uphold the nation's innovation culture. In line with the objectives, the competition served as a platform for young researchers, inventors, and innovators to show-case their products of commercial value.